THE SUNNI-SHI'ITE RIVALRY AND ITS INFLUENCE ON THE GEOPOLITICAL SITUATION OF THE MIDDLE EAST - A. A. Kuznetsov (Vestnik MGIMO-Universiteta, 2014)
The article "The Sunni-Shi'ite rivalry and its influence on the geopolitical situation of the Middle East" is dedicated to the sectarian conflicts in the Middle East region in last 30 years. Author considers the Islamic revolution of 1979 in Iran as the point of departure of this conflict. Author of the article makes a difference between the Shi'ite Islamic revolutionary doctrine of Khomeini and the Salafi Islamic fundamentalism of Saudi Arabia. Author realizes the analysis of the war between Iran and Iraq in 1980-1988. This analysis is emphasized on the regional geopolitical situation and positions of the outside actors (Saudi Arabia, USA, France, Germany). Then it is covered the American invasion of Iraq in 2003 and its geopolitical consequences. To the author's mind this aggression and further empowerment of the Shi'ite majority reduced to the civil war in Iraq and exacerbation of the sectarian conflict. Author of the article considers these events as a part of the geopolitical rivalry between Iran and Saudi Arabia to unfold in the areas of Iraq, Syria and Lebanon.